Stop Blaming the Septum. Issue 1 (January 2016) - Schwarcz, Robert; Fezza, John P.; Jacono, Andrew; Massry, Guy G.
Abstract : Purpose: To identify if isolated surgical violation of the orbital septum predisposes to "middle lamellar" scarring and subsequent postblepharoplasty lower eyelid retraction. Methods: A retrospective review of patients who underwent transconjunctival blepharoplasty in either a postseptal (orbital septum undisturbed) or preseptal (septal incision required) plane was performed. Patients undergoing skin excision, orbicularis muscle plication, and canthal suspension were excluded. The presence of clinically apparent postoperative lower eyelid retraction and limitation of forced superior eyelid excursion (forced traction testing) were assessed. Results: Two hundred eighty-eight patients (576 eyelids) were evaluated. One hundred fifty-eight patients (316 eyelids, 55%) had transconjunctival blepharoplasty performed in a postseptal plane and 130 patients (260 eyelids, 45%) in a preseptal plane. Two hundred two patients (404 eyelids, 70%) had forced traction testing performed postoperatively. After surgery, there were no patient complaints of change in lower eyelid position, subjective physician assessment of clinically apparent lower eyelid retraction, and only 1 case (0.5%) of a positive forced traction test in a patient with conjunctival scarring after significant postoperative infection. Conclusions: Lower eyelid scars leading to eyelid retraction after blepharoplasty are not likely related to " isolated" orbital septal scars (middle lamellar scars). Their designation as a "multilamellar scar" is more appropriate. Abstract : Eyelid scars contributing to postblepharoplasty lower eyelid retraction involve more than the middle lamella (orbital septum) in isolation.